American-Chinese interest in the Horn of Africa Djibouti is a model)) 2000 after a year - Naji محمد نزار (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
China and America have strengthened their influence in Djibouti because of its important geographical location, which overlooks the (Red Sea) and (Bab al-Mandab Strait), which is the global trade route because it transports important energy sources such as white gas, crude black oil, gas and other important sources, so it has become fierce competition for this region between China and America, with the aim of obtaining a place for it in Djibouti and also extending its influence there. Therefore, America has strengthened its presence in Djibouti in several aspects, including: the military through its presence in the (Lemonnier base), by providing health assistance during the days of the Corona epidemic, and through the cultural aspect by teaching the Djiboutian population English. China has strengthened its military presence at the Doraleh base, signed many economic agreements and invested in various fields.